Dynamic interdependence among Nordic stock markets: The role of climate risks - Ho, Thi Hong Minh (My University, 2025)
This study investigates the dynamic return interdependence among Nordic and major global stock markets, as well as the underlying determinants of this connectedness. Applying the Quantile Vector Autoregression (QVAR) framework, this study analyzes twenty-five years of daily data (2000–2024) covering Finland, Sweden, Denmark, and Norway, alongside benchmark indices from the U.S., Europe, Japan, and China. The results show that the level of interdependence within the network is substantially strong at the median quantile, reflecting a high degree of return transmission among these countries. Moreover, return spillovers intensify significantly during both extreme downturns and rallies, indicating that the structure of market linkage is highly state-dependent and asymmetric. The study further finds that peaks in connectedness coincide with major global events such as the Global Financial Crisis, Brexit, the COVID-19 pandemic, and the Russia–Ukraine conflict. At each market level, the U.S., Europe, and Sweden consistently act as net transmitters of shocks, while Denmark and Asian markets typically serve as net receivers. Finland often acts as a transmitter but shifts to a net receiver during periods of crisis. Norway, meanwhile, exhibits relative resilience, maintaining minimal directional connectedness across different market states. Furthermore, the study examines the impact of climate risks and other uncertainty factors on market integration. Ordinary Least Squares (OLS) regressions are conducted using the Total Connectedness Index (TCI) across different quantile levels as the dependent variables. The results indicate that physical risks do not exhibit statistically significant effects within the multivariate framework. In contrast, transition risk and market sentiment emerge as significant drivers of return connectedness, particularly under normal and bearish market conditions. Economic policy uncertainty contributes positively to integration during stable and bullish periods. Likewise, geopolitical risk exerts a negative influence on market linkages. These findings emphasize the importance of incorporating climate transition risks, investor sentiment, and political uncertainty into portfolio construction and risk assessment frameworks. Furthermore, the study points out the value of quantile-based approaches in capturing the nonlinear and regime-dependent nature of financial market interdependence, particularly during turbulent times.
Keywords: fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance